MICROSCOPICAL AND MICROMECHANICAL FEATURES OF HIGH PERFORMANCE CONCRETE CONTAINING LOW LEVELS OF FLY ASH - Vladimír Hrbek; Zdeněk Prošek; Roman Chylík; Lukáš Vráblík (Acta Polytechnica CTU Proceedings, 2019)
Alkali activated fly ash is a widely used admixture to the concrete. Due to the pozzolanic activity, the fly ash can replace up to 60 mass percentage. The impact of fly ash on the concrete depend on the level of it content, i.e. in small levels it improves the macro-mechanical properties and durability as well as chemical resistance. On the other side, fly ash admixture negatively influence the set time and cause slow development of strength. Therefore, the effect of small fly ash admixture levels on the micro-structure of high performance concrete (HPC) is discussed in this study.